Prevalence of Cutibacterium acnes and Staph spp. in the lesions of acne vulgaris in Jakarta - Hermawan, Melyawati; Tjoa, Enty; Hidajat, Inneke J.; Teressa, Maria; Layadi, Eka B.; Wolter, Alegra (UI Scholars Hub, 2021)
Background: Acne vulgaris (AV) is a chronic skin disorder that is commonly seen in young adults. Recent studies have shown that bacteria other than Cuticubacterium acnes found in the skin microbiota also play vital roles in the pathogenesis of AV. Understanding the skin microbiota and its disruption in patients with AV is paramount in treating patients with AV. Methods: Samples were obtained from 36 subjects to evaluate the proportion of Cutibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus in lesions of AV by means of bacterial culture. Results: There were 69 specimens collected from the 36 subjects with AV. The most abundant type of bacteria that was successfully isolated in the cultured AV lesions was Staphylococcus epidermidis(46.4%), followed by Cutibacterium acnes(14.5%), and Staphylococcus aureus(2.9%). Conclusion: Staphylococcus epidermidis,the major species of human skin flora, is the most abundant microorganism found in AV. The development of AV is not necessarily associated with the high proportion of Cutibacterium acnes. More pathogenic bacteria, such as Staphylococcus aureusis also not always found in the AV lesions. These findings may provide the basis for the clinicians to determine which types of antibiotics to prescribe for the treatment of AV.